IFITM5-related (type V) osteogenesis imperfecta with evidence of perinatal involvement: A case report - Valentina Martínez-Montoya; Miguel Angel Fonseca-Sánchez; Gerardo Fabian-Morales; Ramiro Vega-Gamas; Gloria Eugenia Queipo-García; Luis Felipe León-Madero; Luz María Sánchez-Sánchez (Bone Reports, 2024)
Osteogenesis imperfecta (OI) is a rare hereditary disorder characterized by bone fragility and frequent fractures. While most cases are attributed to variations in collagen-coding genes COL1A1 and COL1A2, other genes such as IFITM5 have also been associated with the disease, accounting for up to 5 % of cases. Here, we report a case of a 3-month-old female with a femur fracture and limb deformity. X-rays revealed evidence of osteopenia and previous fractures in the arms, clavicle, ribs, and left limb, alongside prenatal bone deformities detected by ultrasound. Initial clinical evaluation suggested progressively deforming (Sillence's type III) osteogenesis imperfecta (OI). Molecular testing led to the diagnosis of IFITM5-related OI, identifying the c.-14C>T (rs587776916) variant. Although this variant has been previously reported in patients with IFITM5-related OI, prenatal involvement had not been associated with this variant.